Final Report Evaluation of Tools and Metrics to Support Employer Selection of Health Plans - Mattke, Soeren (RAND Corporation, 2014)
The Affordable Care Act places strong emphasis on quality of care as a means to improve outcomes for Americans and promote the financial sustainability of our health care system. This report attempts to help employers understand the structural differences between health plans and the performance dimensions along which plans can differ, as well as to educate employers about available tools that can be used to evaluate plan options.